Application of acoustic emission for determination of initial temperature of casting mould - GOLEC, M.; GOLEC, Z.; Hajkowski, M. (Archives of Acoustics, 2000)
It was shown in this paper that, thermal stresses and accompanying them plastic strains, generated during solidification and cooling of casts of metal alloys, were the sources of acoustic emission. For casts, which phase α is deformed by slip, there is a possibility of determination of initial temperature of casting mould by means of acoustic emission.